2017
DOI: 10.1002/per.2112
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is Knowing: On the Predictive Accuracy of Self– and Informant Reports for Prosocial and Moral Behaviours

Abstract: Under certain circumstances, well‐known others (so‐called informants) may possess unique insights into targets' personality traits beyond the targets' self‐views. Specifically, as proposed by the self–other knowledge asymmetry model, an incremental predictive ability of informants is most likely for traits and corresponding behaviours that are clearly visible to others and highly evaluative in nature. In two studies, we provide an empirical test of this proposition and extend prior research to one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 88 publications
(124 reference statements)
3
31
0
Order By: Relevance
“…The general factor had medium‐sized associations with non‐game measures of altruism, trust, and trustworthiness, including peer‐reports. The general factor's association with self‐reported trustworthiness was only marginally significant and smaller than its association with peer‐reported trustworthiness, which could mean that peers are either abler or more motivated to provide accurate reports of trustworthiness (Thielmann et al, ). The general factor also (negatively) predicted revenge attitudes, suggesting that it is relevant to types of cooperation other than altruism, trust, and trustworthiness.…”
Section: Discussionmentioning
confidence: 98%
“…The general factor had medium‐sized associations with non‐game measures of altruism, trust, and trustworthiness, including peer‐reports. The general factor's association with self‐reported trustworthiness was only marginally significant and smaller than its association with peer‐reported trustworthiness, which could mean that peers are either abler or more motivated to provide accurate reports of trustworthiness (Thielmann et al, ). The general factor also (negatively) predicted revenge attitudes, suggesting that it is relevant to types of cooperation other than altruism, trust, and trustworthiness.…”
Section: Discussionmentioning
confidence: 98%
“…First, the politeness and compassion items of the BFAS were embedded within 100 items measuring a variety of personality domains (e.g., "Believe in the importance of art", "Laugh a lot"), thereby decreasing their salience. Furthermore, all conditions (including the neutrally-framed dictator game) were administered in a similar fashion within the same session, yet the correlation between HEXACO honesty-humility and standard dictator allocations (r = 0.29) was on par with those in previous studies: both where the two had been separated in time (e.g., rs = 0.25, 0.27, 0.29) [5,8,44] and collected together (rs = 0.24, 0.27) [71,72]; for an exception see [73]. These observations are in line with a wider literature showing that prosocial decisions are stable over time and can be consistently predicted by theoretically-relevant measures of personality [74,75].…”
Section: Limitations and Future Directionsmentioning
confidence: 87%
“…The dictator game is interpreted as a measure of prosociality and fairness, and over a hundred studies have shown that dictators are not completely selfish, which suggests that other-regarding concerns are at play [4]. Although dictators allocate on average 28% of the endowment to their partner [4], there is considerable heterogeneity between individuals, which has been linked to personality traits reflecting good manners and fair-mindedness [5][6][7][8][9]. However, a key parameter in transfers of wealth that is absent in the standard dictator game is property ownership and the associated acts of giving or taking.…”
Section: Introductionmentioning
confidence: 99%
“…The present results for the meta-analytically integrated samples were fairly consistent across studies, with only minor variations (see OSF Material 6 at osf.io/m6pb2). Future research could tackle the broader generalizability of our results by applying systematic variations, which could regard sample characteristics (e.g., age groups, situational characteristics, stage or type of relationship to peers who provide adjustment ratings; Paulhus, 1998; see also Carlson, 2016;Leckelt, Küfner, Nestler, & Back, 2015), content domains of self-perceptions (e.g., agentic vs. communal traits, see also Abele et al, 2016;Paulhus & Trapnell, 2008; see public goods games as a potential reality criterion for communal traits, Thielmann, Zimmermann, Leising, & Hilbig, 2017), or the considered adjustment indicators and their measurement perspectives (e.g., mental health ratings provided by acquaintances or by trained observers; Kwan, John, Robins, & Kuang, 2008; physiological and biological health markers, Gramzow et al, 2008).…”
Section: Future Research Directionsmentioning
confidence: 95%